2022
DOI: 10.1002/cnr2.1750
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, prognostic factors, and long‐term outcomes associated with epithelial malignancies of the thymus: A 20‐year single‐institution experience

Abstract: Background: Thymic epithelial tumors are rare and include thymomas and thymic carcinomas. There is scarce literature characterizing prognostic factors and long-term outcomes in these tumors.Aims: This review aims to describe disease features of thymomas and thymic carcinomas and to report clinical differences among thymoma histological subtypes.Methods and Results: A retrospective chart review was performed at the University of Florida Shands Hospital, a tertiary care academic medical center in Gainesville, Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
1
2
1
Order By: Relevance
“…In current study myasthenia gravis had no statistical significance on OAS (p = 0.32) vs (p = 0.082) in the results of Altshuler et al (19) and (p= 0.062) in the results of Nakajima et al (18) . While other studies showed the significance correlation between myasthenia gravis and OAS p <0.05 (22,26) .…”
contrasting
confidence: 65%
See 2 more Smart Citations
“…In current study myasthenia gravis had no statistical significance on OAS (p = 0.32) vs (p = 0.082) in the results of Altshuler et al (19) and (p= 0.062) in the results of Nakajima et al (18) . While other studies showed the significance correlation between myasthenia gravis and OAS p <0.05 (22,26) .…”
contrasting
confidence: 65%
“…The surgery had a statistical significance on OAS had p value <0.01 Altshuler et al (19) vs 0.033 in our study. resectability and ability to get R0 with no residual either microscopic or gross residual is a significant survival prognostic factor in Agrafiotis2022…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Age and overall health are also important prognostic factors. Younger patients and those with good performance status (a measure of general health and ability to carry out daily activities) tend to have better outcomes (43).…”
Section: Malignant Thymomamentioning
confidence: 99%